2014
DOI: 10.1016/j.applanim.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Pain expression is linked to personality in horses

Abstract: Tissue damage may result in pain, inducing protective behaviour such as lameness. Because we cannot directly measure an animal's subjective experience, pain research and veterinary assessment rely on these behavioural indicators when quantifying pain. This assumes that pain expression is proportional to damage but this has not been tested in animals and ignores the possible effects of personality and coping style. First, we assessed whether lameness accurately predicted the severity of tissue damage, or whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…This may suggest that negative changes in affective state that can result from stressful or painful situations may be mediated by stable personality traits. However, only one study to date has focused on the impact of individual differences, such as personality on the experience and expression of pain in animals (Ijichi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that negative changes in affective state that can result from stressful or painful situations may be mediated by stable personality traits. However, only one study to date has focused on the impact of individual differences, such as personality on the experience and expression of pain in animals (Ijichi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also challenging to assess in animals (Merola & Mills, 2015), as it relies on human interpretation of behaviour, and pain behaviours will differ both within and between species. Whilst vets, owners and academics alike are reliant on the assumption that observable signs of pain are indicative of not only the presence of pain but also of the severity of the condition, the study by Ijichi et al (2014) challenged the reliability of this assumption .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that personality in horses affects pain expression (Ijichi et al. ), maternal behaviours (Budzyńska & Krupa ), and learning and memory performance (Christensen et al. ; Valenchon et al.…”
Section: Introductionmentioning
confidence: 99%
“…in both feral and wild populations) and show identifiable interindividual personality differences (Le Scolan et al 1997;Visser et al 2001;Lansade et al 2008a,b). Studies have shown that personality in horses affects pain expression (Ijichi et al 2014), maternal behaviours (Budzy nska & Krupa 2011), and learning and memory performance (Christensen et al 2012;Valenchon et al 2013 The aim of this study was to explore how social network and individual characteristics such as personality influence the organisation of collective movements in a group of domestic horses foraging on a 30-ha pasture. The studied group was entirely composed of females aged between 1 and 6 yrs.…”
Section: Introductionmentioning
confidence: 99%
“…This can be particularly difficult due to a number of other factors affecting how an individual may perceive the pain experienced, including any previous experience of pain they may have had, and when this experience occurred [57,102,103]. An individual's personality may also affect their perception of pain [104], along with their sex [54].…”
Section: Assessing Pain In Farm Animalsmentioning
confidence: 99%